NUTRITION STATUS IN LOW NUTRITION CHILDREN AFTER NUTRITIONAL INTERVENTION IN COVID 19 PANDEMIC - Henita, Yolanda (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Based on the results of the PSG (Nutritional Status Monitoring) in 2017, globally, the prevalence of malnourished children under five was 17.8%, especially in West Java Province, 7.4% of under-five malnutrition 210,155 people. Along with these problems, the government created a PMT (Supplementary Food) program to address nutritional problems in Indonesia. For this reason, this study aims to determine the relationship of supplementary feeding to the improvement of nutritional status of malnourished children under five at Posyandu Anyelir, Pancoranmas District, Depok, with a cross-sectional research design. The data were collected using a questionnaire tested for validity and reliability and carried out anthropometric measurements for toddlers from 0 to 60 months. The result was that 22 out of 33 children (66.7%) experienced malnutrition. There was a significant, significant, strong, unidirectional relationship between changes in nutritional status before and after supplementary feeding (p = 0.004)